Case Report of an Acute Myocardial Infarction as a Result of Spontaneous Coronary Artery Dissection in a Patient with Fibromuscular Dysplasia. (2nd May 2019) - Kalinskaya, A.; Skrypnik, D.; Kostin, A.; Vasilieva, E.; Shpektor, A.
Abstract : Background . Spontaneous coronary artery dissection (SCAD) is an underdiagnosed and rare cause of myocardial infarction (MI). SCAD is defined as the separation of the coronary artery wall by hemorrhage with or without intimal tear. It causes acute coronary syndrome in 1.7% to 4% of cases. Case Summary . We report a case of a patient with acute MI caused by SCAD with marked progression of dissection within 4 days and spontaneous healing in 2 months. Fibromuscular dysplasia (FMD) of the arteries is an associated condition of SCAD that was found in our patient. Conclusion . In young women admitted to the clinic with signs of acute myocardial infarction, SCAD should be suspected. FMD as an associated condition that should be ruled out in every SCAD patient. Conservative treatment of SCAD is the most preferable strategy.